تقييم وتنميّة الموارد المائية في حوض الأبرش (Latakia University Journal -Basic Sciences Series, 2018)
يعالج هذا البحث تقييّم الموارد المائية في حوض نهر الأبرش، جنوب شرق طرطوس، إضافة إلى  تقدير الجريانات السطحية والجوفية، وأظهرت النتائج أن الموارد الحاليّة تزيد عن مجموعة الحاجات لكافة القطاعات، وأن معظم المياه تتجدد مباشرة أو غير مباشرة من مياه الهطول كذلك تم تقدير حجم مياه التغذيّة الصناعية للحوامل الصخريّة المتّصلة هيدروليكياً ببحيرة سد الأبرش بحوالي 10.5 مليون م3. كما شرحنا حركة المياه الجوفيّة في حامل الكريتاسي، ولقد ركزنا على تطوير الموارد المائية المتاحة لتأمين المياه للحاجات الاجتماعيّة والاقتصاديّة في المستقبل ولتحقيق ذلك اقترحنا تنفيذ الوسائل المناسبة.  This study deals with the evaluation of water resources in Abrash basin South East of Tartous. Also estimates the surfaces and sub surfaces flow. The results show that most of the water is replenished directly or indirectly by rainfall and that the value of recent resources is more than total need of all sectors. Moreover the volume of artificiad water rechared in aquifes linked to the lake was estimated about 10.5 m3. The movement and distribution of subsurface water had been explained in Cretaceous Aquifer. we suggest some convenient methods of developing water resources to satisfy future sacial and economic needs. Finally the results of this work have been tabulated and the most important of them are represented graphically.